Media Digital dalam Memberdayakan Kemampuan Berpikir Kritis Abad 21 pada Pembelajaran IPA di Sekolah Dasar - mahirotul hasanah; khusnul qotimah; Amanda, Ita Aula (Indo-MathEdu Intellectuals Journal, 2024)
Digital media plays a crucial role in developing critical thinking skills in science learning in elementary schools in the 21st century. This research aims to explore the impact of using digital media in improving students' critical thinking skills. The literature review research method is carried out by analyzing various books and journals, where students are introduced to science learning through various interactive digital media. In this context, the application of digital media in science learning in elementary schools not only helps students understand scientific concepts, but also empowers them with essential critical thinking skills to face the demands of the 21st century world. The implications of these findings can provide a basis for the development of more innovative and relevant learning strategies in the future.